Leveraging Policy Innovation and Collaboration for Sustainable Growth in Agribusiness and the Green Economy - Dr. Abdul Wahab Samad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2026)
This study examines the role of transitioning to a green economy in the agribusiness sector, encompassing related sectors such as agriculture, fisheries, livestock, forestry, agro-processing industries, and renewable energy. The primary focus is on exploring policies and innovations that support the implementation of a green economy in agribusiness. Data were collected through surveys assessing policies, the adoption of eco-friendly technologies, and their impact on the sustainability of the agribusiness sector. Data analysis, conducted using NVivo 14, identified key themes such as policies promoting green technology adoption, resource efficiency, and carbon emission reduction. The findings reveal that policies supporting green technology and fostering cross-sector collaboration significantly enhance the efficiency and sustainability of agribusiness. These findings underscore the critical role of policy and sectoral collaboration in accelerating the transition to a green economy in agribusiness. This study contributes to understanding how policies and innovations can drive agribusiness transformation toward a sustainable green economy.